A long-distance signaling loop promotes soybean nodulation and productivity - Jingbo Duan; Jinbin Wang; Runze Guo; Chancelor B. Clark; Zhuojun Luo; Xiaochong Li; Leonie Trabert; Xing-Qi Huang; W. Andy Tao; Natalia Dudareva; Gary Stacey; Blake C. Meyers; et al. (Proceedings of the National Academy of Sciences, 2026)
Legume nodulation is initiated when soil bacteria rhizobia infect root hairs and is tightly regulated by host-derived mechanisms that restrict nodule numbers to balance the benefits of symbiotic nitrogen fixation with the plant’s growth and metabolic demands. However, how plants actively promote the initiation of nodulation to counterbalance these restrictive mechanisms and maintain an optimal level of nodulation remains largely unknown. Here, we report a systemic regulatory mechanism through which soybean ( Glycine max ) promotes rhizobial infection. We show that inoculation of soybean roots with rhizobia suppresses the biogenesis of microRNA miR4416-5p in shoots, a mobile microRNA that is transported from shoots to roots. The resulting reduction of miR4416-5p levels in roots enhances the expression of a vegetative lectin gene Lectin 3 ( GmLe3 ), which promotes rhizobial infection, thereby enhancing nodule formation and improving plant productivity under low nitrogen conditions. We further demonstrate that suppression of miR4416-5p biogenesis in shoots is triggered by the root-derived C-TERMINALLY ENCODED PEPTIDE 7 (GmCEP7), establishing a long-distance GmCEP7-miR4416-5p- GmLe3 regulatory loop that is critical for desirable symbiotic synergy and plant productivity. Comparative genomic analysis reveals that this miR4416-5p-mediated regulatory module is absent in the model legumes Medicago truncatula and Lotus japonicus but appears to be conserved in economically important legume crops common bean ( Phaseolus vulgaris ) and pigeonpea ( Cajanus cajan ), suggesting an evolutionary innovation in nodulation control. These findings uncover a systemic mechanism that promotes rhizobial infection and highlight an evolutionary innovation in regulation of nodulation with potential implications for improving legume crop productivity under nitrogen-limited conditions.